Musyahadat Al Fidyu: Youtube-Based Teaching and Learning of Arabic as Foreign Language (AFL) - Albantani, Azkia Muharom; Madkur, Ahmad (Dinamika Ilmu, 2017)
Today, it is not surprising to say that there is a swiftly rising use of internet in education. Internet with the enormous features has provided up prospects for rich and ground-breaking approaches to deal with educational issues and present solutions to the escalating needs for learning resources. Despite this fact, it is still found few studies and practices of utilizing the internet as the media in the field of teaching Arabic as foreign language. This paper specifically focuses on elaborating the use of YouTube in Arabic language classroom. It is attempting to give the answer for some following questions: why using YouTube as Arabic language learning media? How to search for learning resources on YouTube? What Arabic skills and competencies can be trained? How to effectively integrate these resources in the Arabic language classroom? How to do the internet source evaluation? How to find out which the students prefer? What are the strengths and weaknesses of YouTube as learning media? This paper ends its conclusion by recommending the Arabic language teachers to use sources available on YouTube but they must selectively give to the students.